Optimization of the CIDT Model in the MSME Program of the Rokan Hulu Regency Chamber of Commerce and Industry - Alfa Syahputra; Burhan Bungin; Thomas Stefanus Kaihatu; Christina Widya Utami; Liliana Dewi (Jurnal Ilmiah Manajemen Kesatuan, 2025)
With the advancement of time, the programs within the Chamber of Commerce and Industry need to be reconstructed to be more relevant and adaptive to digitalization challenges. The Chamber of Commerce and Industry (Kamar Dagang dan Industri/KADIN) plays a crucial role in supporting SMEs’ growth, yet several obstacles hinder its optimization in Rokan Hulu. Issues such as weak synergy between the chamber of commerce and industry and the local government, overly idealistic policies, lack of attention to small traders, and minimal government involvement in empowering SMEs need urgent solutions. This study aims to explore how the chamber of commerce and industry program reconstruction can optimize digital marketing for SME economic growth in Rokan Hulu. Using the Complexity of Innovation Diffusion Theory as an analytical framework, this qualitative research employs literature review and phenomenological approaches. The findings suggest that strategic reconstruction through competitive selection, digital business incubation, and stakeholder collaboration can enhance SME competitiveness, ensuring sustainable regional economic growth through digital technology adoption.